INTERNET – MEDIUM, PRASA CZY ŚRODOWISKO KOMUNIKACYJNE? - Adamski, Andrzej (Zeszyty Prawnicze, 2016)
PRESS LAW, INTERNET, ONLINE PRESS Summary Article raises the question of the press communications at the Internet. Attempts to answer such questions as: Is the Internet the medium, similar to other media? When an Internet message can be regarded as the press in the meaning of the article 7th of the Polish Press Law? It also indicates that Polish Press Law should be amended and talks over the Ministry of Culture and National Heritage proposals for such amendments.